New Robust Iterative MMSE based Interference Alignment Algorithm - Dinis, Rui (2014)
Interference alignment (IA) is a promising technique for MIMO interference channels based systems, achieving the theoretical bound on degrees of freedom (DoF). However, these gains are reduced in the presence of imperfect channel state information (CSI), due to quantization or channel estimation errors. In this work we propose a new robust iterative IA MMSE-based algorithm, which includes these channel errors in the IA design. The results show that the proposed robust IA algorithm outperforms the known IA-MMSE algorithms, for low to moderate variance of CSI errors.